A polyphenylene sulfide composite material with low expansion coefficient and preparation method thereof

By introducing aminated polyphenylene sulfide into the polyphenylene sulfide resin and reacting with KH560 modified glass fibers, polyphenylene sulfide grafted glass fibers are formed, which solves the problem of high linear expansion coefficient and shrinkage rate of the polyphenylene sulfide composite material, and significantly improves the mechanical properties and molding dimensional stability of the material.

CN119192842BActive Publication Date: 2025-04-08广东塑擎实业有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411459148.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-04-08
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing polyphenylene sulfide composite materials have high linear expansion coefficient and molding shrinkage, resulting in poor dimensional stability and poor compatibility between glass fiber and polyphenylene sulfide, which affects the mechanical properties of the material.

Method used

By introducing aminated polyphenylene sulfide into the polyphenylene sulfide resin and reacting with epoxy groups on the surface of KH560 modified glass fibers, polyphenylene sulfide grafted glass fibers are formed, and the compatibility between the glass fibers and the polyphenylene sulfide resin is improved, and it is melt blended with the polyphenylene sulfide resin.

Benefits of technology

The linear expansion coefficient and shrinkage rate of polyphenylene sulfide composite material are significantly reduced, the bending strength, bending modulus and impact strength of the material are improved, and the molding dimensional stability of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091370280000021
    Figure BDA0005091370280000021
  • Figure BDA0005091370280000071
    Figure BDA0005091370280000071
Patent Text Reader

Abstract

The invention relates to the technical field of polyphenylene sulfide, and discloses a polyphenylene sulfide composite material with a low expansion coefficient and a preparation method thereof. The polyphenylene sulfide composite material with a low expansion coefficient comprises 100 parts by weight of a polyphenylene sulfide resin, 10-50 parts by weight of polyphenylene sulfide grafted glass fibers, and 0.3-0.7 parts by weight of an antioxidant. The invention melt-blends the polyphenylene sulfide grafted glass fibers with the polyphenylene sulfide resin, and due to the polyphenylene sulfide molecular chains grafted on the surface of the glass fibers, the compatibility between the glass fibers and the polyphenylene sulfide resin is improved, the interface performance between the two is improved, the glass fibers have a better reinforcing effect, the bending strength, the bending modulus and the impact strength are significantly increased, the linear expansion coefficient and the shrinkage rate are significantly reduced, and the molding dimensional stability of the material is very good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyphenylene sulfide, in particular to a polyphenylene sulfide composite material with a low expansion coefficient and a preparation method thereof. Background Art

[0002] Polyphenylene sulfide is a high-performance polymer resin material with important applications in automobile transportation, machinery manufacturing, aerospace, etc. Reducing the linear expansion coefficient and molding shrinkage of polyphenylene sulfide, improving its dimensional stability, and enhancing its mechanical strength and other properties can make polyphenylene sulfide have better practical applications in precision instruments, microelectronics, etc.

[0003] At present, the modification of polyphenylene sulfide mainly includes blending modification, ultraviolet light irradiation modification, grafting modification and other methods, among which blending modification has the advantages of simple operation, simple process, and diverse filling modifiers. Glass fiber is an inorganic non-metallic fiber material with excellent mechanical properties and good high temperature resistance. Improving the compatibility of the interface performance between glass fiber and polyphenylene sulfide is a research difficulty. Patent CN113861687B discloses a polyphenylene sulfide composition and a preparation method thereof, using polyphenylene sulfide resin, glass fiber, long-chain alkyl acylated modified polyphenylene sulfide, epoxy-containing compatibilizer and the like as raw materials, and the obtained polyphenylene sulfide composition has excellent processing properties and mechanical properties. However, the patent does not reduce the linear expansion coefficient and shrinkage rate of polyphenylene sulfide, and does not improve its molding dimensional stability. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a polyphenylene sulfide composite material with a low expansion coefficient and a preparation method thereof, thereby solving the problem of poor compatibility between glass fiber and polyphenylene sulfide and reducing the expansion coefficient of polyphenylene sulfide.

[0005] The technical solution provided by the present invention is: a polyphenylene sulfide composite material with a low expansion coefficient, comprising 100 parts by weight of polyphenylene sulfide resin, 10-50 parts by weight of polyphenylene sulfide grafted glass fiber, and 0.3-0.7 parts by weight of antioxidant.

[0006] The preparation method of polyphenylene sulfide grafted glass fiber comprises: adding amino polyphenylene sulfide to N,N-dimethylformamide, stirring evenly, adding KH560 modified glass fiber, heating to 60-75°C, stirring and reacting for 12-24h, removing N,N-dimethylformamide by reduced pressure distillation, and drying to obtain polyphenylene sulfide grafted glass fiber.

[0007] Among them, the mass ratio of amino polyphenylene sulfide and KH560 modified glass fiber is (0.4-1.2):1.

[0008] Wherein, the preparation method of amination polyphenylene sulfide comprises:

[0009] (1) Add polyphenylene sulfide resin to 1,2-dichloroethane, stir until swelling, then add chloromethyl methyl ether and tin tetrachloride, heat to 50-60°C in a nitrogen atmosphere, stir and react for 24-48 hours, cool, add the polyphenylene sulfide resin to a hydrochloric acid solution and soak, then extract and purify with ethanol, wash with water, and dry to obtain chloromethylated polyphenylene sulfide.

[0010] (2) Add chloromethylated polyphenylene sulfide and diethylenetriamine to N,N-dimethylformamide, heat to 80-110°C, stir and react for 24-36 hours, pour the solution into water after cooling, filter, wash with ethanol and water, and dry to obtain amino polyphenylene sulfide. The reaction route is as follows:

[0011]

[0012] Among them, the mass ratio of polyphenylene sulfide resin, chloromethyl methyl ether and tin tetrachloride in (1) is 1:(14-20):(1.2-1.8).

[0013] Among them, the mass ratio of chloromethylated polyphenylene sulfide and diethylenetriamine in (2) is 1:(0.8-2.5).

[0014] The preparation method of KH560 modified glass fiber includes: adding KH560 and glass fiber into water, stirring and dispersing, reacting in a nitrogen atmosphere, filtering, washing with ethanol, and drying to obtain KH560 modified glass fiber.

[0015] The preparation method of the low expansion coefficient polyphenylene sulfide composite material comprises: adding polyphenylene sulfide resin, polyphenylene sulfide grafted glass fiber and antioxidant into a twin-screw extruder for melt extrusion, the temperature of sections 1-6 is 255-290°C, pelletizing and obtaining the low expansion coefficient polyphenylene sulfide composite material.

[0016] Technical effect: The present invention utilizes chloromethyl methyl ether to chloromethylate polyphenylene sulfide, and then reacts it with diethylenetriamine to obtain amino polyphenylene sulfide, and the introduced amino group reacts with the epoxy group on the surface of KH560 modified glass fiber, thereby introducing polyphenylene sulfide molecular chains on the surface of the glass fiber to obtain polyphenylene sulfide grafted glass fiber, thereby realizing the surface functional modification of the glass fiber.

[0017] The present invention melt-blends polyphenylene sulfide grafted glass fiber and polyphenylene sulfide resin. Due to the polyphenylene sulfide molecular chain grafted on the surface of the glass fiber, the compatibility between the glass fiber and the polyphenylene sulfide resin is improved, the interface performance between the two is improved, the glass fiber has a better reinforcement effect, the bending strength, bending modulus and impact strength are significantly increased, the linear expansion coefficient and shrinkage rate are significantly reduced, and the molding size stability of the material is very good. DETAILED DESCRIPTION

[0018] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0019] Glass fiber, specification is 3-4.5mm, Taian Haosong Fiber Co., Ltd.

[0020] Example 1

[0021] (1) Add 15 g KH560 and 80 g glass fiber to 1 L water, stir and disperse, heat to 70 ° C in a nitrogen atmosphere, stir and react for 2 h, filter, wash with ethanol, and dry to obtain KH560 modified glass fiber.

[0022] (2) Add 15 g of polyphenylene sulfide resin to 140 mL of 1,2-dichloroethane, stir until swelling, then add 270 g of chloromethyl methyl ether and 24 g of tin tetrachloride, heat to 60 ° C in a nitrogen atmosphere, stir and react for 48 hours, cool, add the polyphenylene sulfide resin to a hydrochloric acid solution and soak, then extract and purify with ethanol, wash with water, and dry to obtain chloromethylated polyphenylene sulfide.

[0023] (3) Add 20 g of chloromethylated polyphenylene sulfide and 40 g of diethylenetriamine to 350 mL of N,N-dimethylformamide, heat to 110°C, stir and react for 24 hours, and after cooling, pour the solution into water, filter, wash with ethanol and water, and dry to obtain amino polyphenylene sulfide.

[0024] (4) Add 40 g of amino polyphenylene sulfide to 2 L of N,N-dimethylformamide, stir evenly, add 100 g of KH560 modified glass fiber, heat to 60°C, stir and react for 18 h, remove N,N-dimethylformamide by vacuum distillation, and dry to obtain polyphenylene sulfide grafted glass fiber.

[0025] (5) Add 1 kg of polyphenylene sulfide resin, 100 g of polyphenylene sulfide grafted glass fiber, and 6 g of antioxidant 1010 into a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 are 255° C., 270° C., 290° C., 290° C., 280° C., and 280° C. Pelletizing is performed to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0026] Example 2

[0027] (1) Add 15 g of polyphenylene sulfide resin to 120 mL of 1,2-dichloroethane, stir until swelling, then add 210 g of chloromethyl methyl ether and 18 g of tin tetrachloride, heat to 60 ° C in a nitrogen atmosphere, stir and react for 24 hours, cool, add the polyphenylene sulfide resin to a hydrochloric acid solution and soak, then extract and purify with ethanol, wash with water, and dry to obtain chloromethylated polyphenylene sulfide.

[0028] (2) Add 20 g of chloromethylated polyphenylene sulfide and 16 g of diethylenetriamine to 300 mL of N,N-dimethylformamide, heat to 100°C, stir and react for 24 hours, and after cooling, pour the solution into water. After filtering, wash with ethanol and water, and dry to obtain amino polyphenylene sulfide.

[0029] (3) Add 65 g of amino polyphenylene sulfide to 2.5 L of N,N-dimethylformamide, stir evenly, add 100 g of KH560 modified glass fiber (prepared in the same way as in Example 1), heat to 75 ° C, stir and react for 12 h, remove N,N-dimethylformamide by vacuum distillation, and dry to obtain polyphenylene sulfide grafted glass fiber.

[0030] (4) Add 1 kg of polyphenylene sulfide resin, 200 g of polyphenylene sulfide grafted glass fiber, and 7 g of antioxidant 1010 into a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 are 255°C, 270°C, 290°C, 290°C, 280°C, and 280°C. Pelletize to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0031] Example 3

[0032] (1) Add 15 g of polyphenylene sulfide resin to 150 mL of 1,2-dichloroethane, stir and swell, then add 300 g of chloromethyl methyl ether and 27 g of tin tetrachloride, heat to 50 ° C in a nitrogen atmosphere, stir and react for 48 hours, cool, add the polyphenylene sulfide resin to a hydrochloric acid solution and soak, then extract and purify with ethanol, wash with water, and dry to obtain chloromethylated polyphenylene sulfide.

[0033] (2) Add 20 g of chloromethylated polyphenylene sulfide and 50 g of diethylenetriamine to 400 mL of N,N-dimethylformamide, heat to 100°C, stir and react for 36 hours, and after cooling, pour the solution into water, filter, wash with ethanol and water, and dry to obtain amino polyphenylene sulfide.

[0034] (3) Add 90 g of amino polyphenylene sulfide to 3 L of N,N-dimethylformamide, stir evenly, add 100 g of KH560 modified glass fiber (prepared in the same way as in Example 1), heat to 70° C., stir and react for 24 h, remove N,N-dimethylformamide by vacuum distillation, and dry to obtain polyphenylene sulfide grafted glass fiber.

[0035] (4) Add 1 kg of polyphenylene sulfide resin, 300 g of polyphenylene sulfide grafted glass fiber, and 5 g of antioxidant 1010 into a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 are 255°C, 270°C, 290°C, 290°C, 280°C, and 280°C. Pelletize to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0036] Example 4

[0037] (1) Add 15 g of polyphenylene sulfide resin to 120 mL of 1,2-dichloroethane, stir until swelling, then add 240 g of chloromethyl methyl ether and 21 g of tin tetrachloride, heat to 50 ° C in a nitrogen atmosphere, stir and react for 36 hours, cool, add the polyphenylene sulfide resin to a hydrochloric acid solution and soak, then extract and purify with ethanol, wash with water, and dry to obtain chloromethylated polyphenylene sulfide.

[0038] (2) Add 20 g of chloromethylated polyphenylene sulfide and 28 g of diethylenetriamine to 350 mL of N,N-dimethylformamide, heat to 80°C, stir and react for 36 hours, pour the solution into water after cooling, filter, wash with ethanol and water, and dry to obtain amino polyphenylene sulfide.

[0039] (3) Add 120 g of amino polyphenylene sulfide to 3 L of N,N-dimethylformamide, stir evenly, add 100 g of KH560 modified glass fiber (prepared in the same way as in Example 1), heat to 70° C., stir and react for 24 h, remove N,N-dimethylformamide by vacuum distillation, and dry to obtain polyphenylene sulfide grafted glass fiber.

[0040] (4) Add 1 kg of polyphenylene sulfide resin, 400 g of polyphenylene sulfide grafted glass fiber, and 3 g of antioxidant 1010 into a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 are 255°C, 270°C, 290°C, 290°C, 280°C, and 280°C. Pelletize to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0041] Example 5

[0042] (1) Add 1 kg of polyphenylene sulfide resin, 500 g of polyphenylene sulfide grafted glass fiber (prepared in the same manner as in Example 1), and 6 g of antioxidant 1010 into a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 are 255°C, 270°C, 290°C, 290°C, 280°C, and 280°C. Pelletizing is performed to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0043] Comparative Example 1

[0044] (1) Add 1 kg of polyphenylene sulfide resin and 6 g of antioxidant 1010 into a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 are 255°C, 270°C, 290°C, 290°C, 280°C, and 280°C. Pelletize to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0045] Comparative Example 2

[0046] (1) 1 kg of polyphenylene sulfide resin, 100 g of glass fiber, and 6 g of antioxidant 1010 were added to a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 were 255° C., 270° C., 290° C., 290° C., 280° C., and 280° C. The pellets were cut to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0047] Comparative Example 3

[0048] (1) 1 kg of polyphenylene sulfide resin, 100 g of KH560 modified glass fiber (prepared in the same manner as in Example 1), and 6 g of antioxidant 1010 were added to a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 were 255° C., 270° C., 290° C., 290° C., 280° C., and 280° C. The mixture was pelletized to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0049] Comparative Example 4

[0050] (1) Add 40 g of chloromethylated polyphenylene sulfide (prepared in the same manner as in Example 1) to 2 L of N,N-dimethylformamide, stir evenly, add 100 g of KH560 modified glass fiber, heat to 60° C., stir for 18 h, remove N,N-dimethylformamide by vacuum distillation, and dry to obtain a polyphenylene sulfide-glass fiber material.

[0051] (2) Add 1 kg of polyphenylene sulfide resin, 100 g of polyphenylene sulfide-glass fiber material, and 6 g of antioxidant 1010 into a twin-screw extruder for melt extrusion. The temperatures of sections 1-6 are 255° C., 270° C., 290° C., 290° C., 280° C., and 280° C. Pelletizing is performed to obtain a polyphenylene sulfide composite material with a low expansion coefficient.

[0052] High-strength glass fiber reinforced modified polyphenylene sulfide was injection molded by an injection molding machine. The three sections of the injection molding machine were 280℃, 290℃, and 295℃. The temperature was used to make standard specimens. Performance tests were carried out. The bending performance was tested according to GB / T 9341-2008. The notched impact strength was tested according to GB / T 1843-2008. The linear expansion coefficient was tested according to GB / T 1036-2008. The shrinkage rate was tested according to GB / T 17037.4-2003. The test results are shown in Table 1.

[0053] Table 1: Effect test

[0054]

[0055]

[0056] After testing, it was found that the polyphenylene sulfide material of Comparative Example 1 did not have glass fiber added, and had low flexural strength, flexural modulus and impact strength, and had large linear expansion coefficient and shrinkage rate, and poor molding dimensional stability of the material.

[0057] In Comparative Example 2, glass fiber was added. Due to the poor compatibility between glass fiber and polyphenylene sulfide resin, it was difficult to effectively improve the mechanical properties of the material, resulting in a small increase in bending strength, bending modulus and impact strength. In addition, glass fiber and polyphenylene sulfide were prone to form interface defects, and the linear expansion coefficient and shrinkage rate were not significantly reduced, and the molding dimensional stability of the material was poor.

[0058] The glass fiber of comparative example 3 is modified by KH560 to improve the compatibility with polyphenylene sulfide resin, so that the glass fiber has a good reinforcement effect, improves the bending strength, bending modulus and impact strength of the material, and reduces the linear expansion coefficient and shrinkage rate, and the material has good molding dimensional stability.

[0059] In Example 1-5, amino polyphenylene sulfide is reacted with the epoxy groups on the surface of KH560 modified glass fiber to introduce polyphenylene sulfide molecular chains on the surface of the glass fiber, and then melt-blended with the polyphenylene sulfide resin, thereby further improving the compatibility between the glass fiber and the polyphenylene sulfide resin and improving the interface performance between the two, so that the glass fiber has a better reinforcement effect, the bending strength, bending modulus and impact strength are significantly increased, and the linear expansion coefficient and shrinkage rate are significantly reduced, and the molding dimensional stability of the material is very good.

[0060] The chloromethylated polyphenylene sulfide of Comparative Example 4 does not contain an amino group and cannot react with the epoxy group of the KH560 modified glass fiber. The polyphenylene sulfide-glass fiber material is in a blended state, and the glass fiber is not grafted with a polyphenylene sulfide molecular chain. When melt-blended with the polyphenylene sulfide resin, the compatibility between the glass fiber and the polyphenylene sulfide resin is not improved. The bending strength, bending modulus and impact strength of the material are lower than those of the embodiments, and the linear expansion coefficient and shrinkage rate are larger.

[0061] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A polyphenylene sulfide composite material with a low expansion coefficient, characterized in that: The low expansion coefficient polyphenylene sulfide composite material comprises 100 parts by weight of polyphenylene sulfide resin, 10-50 parts by weight of polyphenylene sulfide grafted glass fiber, and 0.3-0.7 parts by weight of antioxidant; The preparation method of the polyphenylene sulfide grafted glass fiber comprises: adding amino polyphenylene sulfide to N,N-dimethylformamide, stirring evenly, adding KH560 modified glass fiber, heating and stirring to react, removing N,N-dimethylformamide by vacuum distillation, and drying to obtain the polyphenylene sulfide grafted glass fiber.

2. The low expansion coefficient polyphenylene sulfide composite material according to claim 1, characterized in that: The mass ratio of the amino polyphenylene sulfide and KH560 modified glass fiber is (0.4-1.2):

1.

3. The low expansion coefficient polyphenylene sulfide composite material according to claim 1, characterized in that: The reaction temperature is 60-75°C and the reaction time is 12-24h.

4. The low expansion coefficient polyphenylene sulfide composite material according to claim 2, characterized in that: The preparation method of the amino polyphenylene sulfide comprises: (1) Add polyphenylene sulfide resin to 1,2-dichloroethane, stir and swell, then add chloromethyl methyl ether and tin tetrachloride, heat to 50-60° C. in a nitrogen atmosphere, stir and react for 24-48 hours, cool and soak the polyphenylene sulfide resin in a hydrochloric acid solution, then extract and purify with ethanol, wash and dry to obtain chloromethylated polyphenylene sulfide; (2) Add chloromethylated polyphenylene sulfide and diethylenetriamine to N,N-dimethylformamide, heat and stir to react, pour the solution into water after cooling, filter, wash and dry to obtain amino polyphenylene sulfide.

5. The low expansion coefficient polyphenylene sulfide composite material according to claim 4, characterized in that: The mass ratio of polyphenylene sulfide resin, chloromethyl methyl ether and tin tetrachloride in (1) is 1:(14-20):(1.2-1.8).

6. The low expansion coefficient polyphenylene sulfide composite material according to claim 4, characterized in that: The mass ratio of chloromethylated polyphenylene sulfide to diethylenetriamine in (2) is 1:(0.8-2.5).

7. The low expansion coefficient polyphenylene sulfide composite material according to claim 4, characterized in that: The reaction temperature in (2) is 80-110° C. and the reaction time is 24-36 hours.

8. The low expansion coefficient polyphenylene sulfide composite material according to claim 2, characterized in that: The preparation method of the KH560 modified glass fiber comprises: adding γ-glycidyloxypropyltrimethoxysilane and glass fiber into water, stirring and dispersing, reacting in a nitrogen atmosphere, filtering, washing with ethanol, and drying to obtain the KH560 modified glass fiber.

9. A method for preparing a polyphenylene sulfide composite material with a low expansion coefficient as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises: adding polyphenylene sulfide resin, polyphenylene sulfide grafted glass fiber and antioxidant into a twin-screw extruder for melt extrusion, setting the temperature of sections 1 to 6 at 255-290° C., pelletizing and obtaining a polyphenylene sulfide composite material with a low expansion coefficient.

Citation Information

Patent Citations

  • A polyphenylene sulfide composition and its preparation method

    CN113861687B

  • Battery pack box refractory material and preparation method thereof

    CN111087814A

  • Polyphenylene sulfide composite material with low dielectric constant and preparation process thereof

    CN112280301A